Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:
- 53, - 207, - 7
Step-by-step explanation:
To obtain f(- 2), substitute x = - 2 into f(x), that is
f(- 2) = - 9(- 2)² + 5(- 2) - 7 = - 9(4) - 10 - 7 = - 36 - 10 - 7 = - 53
(b)
Similarly substitute x = 5 into f(x)
f(5) = - 9(5)² + 5(5) - 7 = - 9(25) + 25 - 7 = - 225 + 25 - 7 = - 207
(c)
f(0) = - 9(0)² + 5(0) - 7 = 0 + 0 - 7 = - 7
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.